Karakteristik Ibu Yangmengalami Depresi Postpartum - Ratu Kusuma (Universitas Batanghari Jambi, 2019)
In a condition, pregnancy is defined as a crisis condition so that the women experience various psychological disorder, one of that is depression. Depression during pregnancy can continue in the postpartum period. Postpartum depression is characterized by feeling of sadness, crying, anxiety, fear, feeling lonely, suspicious, decreased appetite, sleep disorder, difficulty concentrating, feeling of worthlessness, loss of hope, lack of interest in the baby, and feeling of being unable to become mother, even in some cases of hallucinations so that there is an attempt by mothers to divorce babies, themselves or others These symptoms appear after the second week postpartum and can even continue for up to 2 years. The incidence of postpartum depression in the world reaches 20%, Asia is 15-20%, Indonesia is 15-20% and Riau Province is 20%. The purpose of this study is to identify the characteristic of mother who experience postpartum depression. This research is a descriptive study, with consecutive sampling technique, carried out on 24 postpartum women in Kecamatan Bangkinang Kota and 30 postpartum women in Kecamatan Kuok. Using demographic instrument and Edinburgh postpartum depression scale (EPDS). The result showed, some postpartum women were at the age of not risk (88.89%), primary-secondary (72.22%), not working (61.11%), parity is multipara (72.22%), number of children 0-4, never abortion (87.04%), wanted pregnancy (81.48%), gestational age is mature (79.63%), normal labor (87.04%) and 7 (12.96%) postpartum women experience postpartum depression. Depression experienced by postpartum women in Kecamatan Bangkinang Kota and Kecamatan Kuok is quite high, this is thought to be caused by factors of employment, educational degree, number of children and unwanted pregnancy.